The changing landscape of infective endocarditis in South Africa - de Villiers, Marthinus Coenraad (Department of Medicine, 2020)
Background. Little is known about the current clinical profile and outcomes of patients with infective endocarditis (IE) in South Africa. Methods. We conducted a retrospective review of the records of patients admitted to Groote Schuur Hospital between 2009 and 2016 fulfilling universal criteria for definite or possible IE, in search of demographic, clinical, microbiological, echocardiographic, treatment and outcome information. Results. 105 patients fulfilled the modified Duke criteria for IE. The median age of the cohort was 39 years (IQR 29-51), with a male preponderance (61.9%). The majority of patients (72.4%) had left-sided native valve endocarditis, 14% had right-sided disease, and 13.3% had prosthetic valve endocarditis. A third of the cohort had rheumatic heart disease. Although 41.1% of patients with left-sided disease had negative blood cultures, the three most common organisms cultured in this subgroup were Staphylococcus aureus (18.9%), Streptococcus spp. (16.7%) and Enterococcus spp. (6.7%). Participants with right-sided endocarditis were younger (29 years (IQR 27-37)), were predominantly intravenous drug users (IVDU; 73.3%) and the majority cultured positive for S. aureus (73.3%) with frequent septic pulmonary complications (40.0%). The overall in-hospital mortality was 16.2%, with no deaths in the group with right-sided endocarditis. Predictors of death in our patients were heart failure (OR 8.16, CI 1.77-37.70; p=0.007) and an age > 45 years (OR 4.73, CI 1.11- 20.14; p=0.036). Valve surgery was associated with a reduction in mortality (OR 0.09, CI 0.02-0.43; p=0.003). Conclusions. Infective endocarditis in a typical teaching tertiary care centre in South Africa remains an important clinical problem. In this setting, it continues to affect mainly young people with post-inflammatory valve disease and congenital heart disease. IE is associated with an in-hospital mortality that remains high. Intravenous drug-associated endocarditis caused by S. aureus is an important IE subset, comprising approximately 10% of all cases, a fact which was not reported 15 years ago, and culture-negative endocarditis remains highly prevalent. Heart failure in IE carries significant risk of death and needs a more intensive level of care in hospital. Finally, cardiac surgery was associated with reduced mortality, with the largest impact in those patients with heart failure.